PENGUATAN KARAKTER DAN KEPEMIMPINAN KRISTEN PESERTA DIDIK MELALUI LDKK DI SMP ERENOS - Roedy Silitonga; Devy Stany Walukow; Ferdinandus Butarbutar (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
Christian Leadership Training (LDKK) is an integral part of character education that begins in the family, church, and school. The basic principle is to prepare students to be responsible, servant leaders who are rooted in the knowledge of God. The goal is to discover, train, and develop the leadership potential of students so that they are equipped to be future leaders who emulate Christ. At Erenos Junior High School, this program is implemented through a combination of LDKK and Community Service (PKM) held by lecturers, emphasizing the value of humility in accordance with the principle of “He must increase” (John 3:30). The activities took the form of leadership training, spiritual guidance, and service activities that took place on Wednesday, October 23, 2024, in Lubana Sengkol, South Tangerang, and were attended by 132 students. The expected outcome is the creation of a generation of Christian leaders who know God personally and are committed to spiritual, academic, and social life. The findings of the activity show that students are becoming more aware of their identity as children of God and understand their calling to lead with love and godly character in their daily lives.